Germinación y supervivencia al repique de Anthocephalus cadamba Miq. (Kadam) - González Rivadeneyra, M.C.; Instituto Interamericano de Ciencias Agrícolas (IICA) (IICA, Turrialba (Costa Rica), 2014)
Tesis (Mag.Sc.) - IICA, Turrialba (Costa Rica), 1968